EVALUASI KETERSEDIAAN OBAT KRONIS UNTUK PASIEN RUJUK BALIK BPJS PADA MASA PANDEMI PERIODE OKTOBE – DESEMBER TAHUN 2020 - Valiandri Puspadina (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
Social security is a form of social protection to ensure that all people can meet their basic needs for a decent life. The social security system is the procedure for administering the social security program. The Social Security Administering Body (BPJS) is a legal entity established to administer the national social system program. Apotek X is one of the pharmacies in the city of Surabaya which is a referral pharmacy for BPJS participants. The availability of drugs in pharmacies will determine the achievement of an optimal health service. One of the pharmacy's efforts is to manage the availability of drugs for the better. The results of observations made are that there is a discrepancy between drug procurement and drug use. The purpose of this study was to evaluate the availability of chronic drugs at Apotek X Surabaya. This research is a nonexperimental study using a retrospective method. This research was conducted at Apotek X Surabaya. Method of data collection This study used secondary data derived from the prescription of patients referred back. From the results of the study, it can be seen from the amount of drug suitability obtained by 79.94%, the amount of drug availability obtained by 59.12%, and the number of drugs given by 80.97%. The conclusion of this research is that it can be concluded that the results of chronic drug availability at pharmacy X Surabaya by comparing the number of drugs prescribed with the number of drugs dispensed are obtained with the level of drugs in the pharmacy in good category